2012
DOI: 10.1097/sla.0b013e31823000ed
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of Whole Sentinel Lymph Node Analysis by One-Step Nucleic Acid Amplification for Intraoperative Diagnosis of Breast Cancer Metastases

Abstract: Objective: To assess the reliability of using the One-Step Nucleic Acid Amplification (OSNA) assay as a single test on whole sentinel lymph nodes (SLN) as a method of intraoperative diagnosis and staging of SLNs in breast cancer.Background: Combining histological and molecular assessment of metastasis on the same SLN may not fully reproduce the actual load of cancer cells present in the SLN and create problems in decisions regarding axillary dissection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
54
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(60 citation statements)
references
References 43 publications
5
54
1
Order By: Relevance
“…This is a limitation of such studies, yet there is no way of avoiding it. It would be interesting to perform OSNA examination on the whole lymph node, as is done in breast cancer [45,46]. Unfortunately, since no studies evaluating the accuracy of OSNA in thyroid cancer have been carried out, it is impossible, from an ethical and legal point of view, to perform OSNA instead of histopathology.…”
Section: Prace Oryginalnementioning
confidence: 99%
“…This is a limitation of such studies, yet there is no way of avoiding it. It would be interesting to perform OSNA examination on the whole lymph node, as is done in breast cancer [45,46]. Unfortunately, since no studies evaluating the accuracy of OSNA in thyroid cancer have been carried out, it is impossible, from an ethical and legal point of view, to perform OSNA instead of histopathology.…”
Section: Prace Oryginalnementioning
confidence: 99%
“…Two 52,59 of the cohort studies reveal reasonably homogeneous patient populations with regard to age and clinical status. A relatively small sample size was used for each patient group in the study reported by Guillen-Paredes, 56 with a difference of ∼7 years for mean age.…”
Section: One-step Nucleic Acid Amplificationmentioning
confidence: 99%
“…Sixteen test accuracy papers were included for OSNA, [50][51][52][53][54][55][56][57][58][59][60][61][62][63][64][65] with two papers reporting the same study. Two unpublished papers 40,66 for Metasin were identified and assessed using the Standards for the Reporting of Diagnostic Accuracy Studies (STARD) in Table 7.…”
Section: Number and Description Of Included Studiesmentioning
confidence: 99%
“…Photographic documentation of sampling is extremely helpful in this respect and for accurate evaluation of the status of resection margins (Figure 1). The examination of sentinel lymph node after NAT should be as accurate as possible, but molecular test (such as One Step Nucleic Acid Amplification assay, ie, OSNA (19)) and immunocytochemistry for cytokeratins are not recommended (20).…”
Section: Gross Handling and Reporting Of Surgical Specimens After Natmentioning
confidence: 99%